Ertebøllekunstens teknik og kronologi: Nye fund fra den jyske Ertebøllekultur - H. Andersen, Søren (Kuml, 2025)
Ertebølle art – techniques and chronology New finds from the Ertebølle culture in Jutland This article presents a new tool type within the material equipment of the Ertebølle culture in Jutland (figs. 1-2). The artefact is made of red deer antler and has a polished surface. The outline is oblong with parallel edges; one end is blunt, while the other ends in a break. The cross-section is semicircular, and on the top side is a small tap (figs. 1-2). The new artefact is, moreover, decorated with various patterns, in the rare pointillé (punch) technique and with both fine and deeply incised lines. The new type is extremely uncommon and has not previously been found in Jutland, but a few examples have been recorded on Ertebølle settlements in northern Funen and eastern Zealand (figs. 3-5). The scarcity of the finds means that a secure identification of the tool’s function is not possible, but it is found in both the Early and Late Ertebølle culture. Besides Numerous new ornamented Ertebølle artefacts have turned up since the two overviews of the art of the Ertebølle culture were published in Kuml in 1981 and 1998 (see note 60) (figs. 1-25). Most comprise antler axes, but there is also a single shaft (fig. 12) and a fragment of a bone knife ornamented with drilled pits and a rare depiction of a human figure (fig. 20). Most of the new finds derive from central-eastern Jutland, especially the area around Horsens Fjord, and on Djursland which, both in a Danish and a northern European context, constitute areas yielding many ornamented Late Mesolithic antler artefacts. The new finds also include two antler axes (figs. 6 and 11) and a slender shaft (fig. 7). The surface of the antler axe, which is worn smooth, is covered by several different incised patterns, for example, zigzag bands of thin lines, bunches of short, parallel lines, a rhombus and a row of the familiar ‘wheatsheaf’ motifs. All these motifs are incised into the surface of the antler axe using fine, thin lines (fig. 6). Surface-covering ornamentation is a characteristic feature of tools from the Early Ertebølle culture and, with the aid of ‘surface stratigraphy’, it has been possible to distinguish and date various decorative techniques and episodes in relation to each other (fig. 27). The stab technique is the earliest, while that employing fine, thin lines is slightly later. The latest patterns are those which are incised in a technique employing broader, deeper lines. It is possible that a small group of antler axes with a characteristic smooth-scraped surface (figs. 22-25) represents the latest decorative technique employed during the Ertebølle culture. After this technique, no further examples of the decoration of Ertebølle antler artefacts are found. The ornamented antler axes can be divided into two groups: A small group of heavily worn examples that have been used over a longer period and which bear several successive incised patterns employing different techniques, compositions and motifs, and a larger group of axes that do not have a worn surface and only bear a few motifs of an individual character. The first group can be interpreted as ‘ritual/magical’ pieces that have been used over a long period, while the second group represents the more individual, identity-marked artefacts with a looser, less stringent decorative structure. The ritual use of the axes in the first group has extended over such a long time span that both the decorative techniques and the motifs have changed several times. This decorative sequence can be roughly dated to the earliest/Early Ertebølle culture, c. 5400-4700 BC. The shaft (fig. 7) is unusual, given that it is made from a very slender (young) antler of atypical size and form and displays very regular ornamentation in the form of a panel containing a long row of wheatsheaves. A similar slender shaft bearing wheatsheaf ornamentation has been recorded from the submerged Ertebølle locality of Ellerbek in Kieler Förde, and these two shafts constitute a small group of the ornamented shafts from the Ertebølle culture. They are related in form to the throwing sticks of late ice age times. The commonest motif employed in the Ertebølle culture of western Denmark is the wheatsheaf, which is found on c. 25 antler axes. It is characteristic that this motif almost always appears as well-delimited ‘sets’ on the axes (13 examples), while it has a more scattered occurrence across the surface of other artefacts. A count of the number of wheatsheaves in the motif groups on the individual tools shows that in most cases (16 examples) there is a clear dominance of sets containing groups of three, four or five motifs, whereas one or two wheatsheaves are rare occurrences. Conversely, there are only three cases where more than ten motifs have been incised on the same artefact. In one instance (the antler from Bogø Nor) as many as about 25 motifs occur on the same piece. The fact that the motifs only rarely show a slight overlap indicates the ornamentation was not planned as a single composition from the beginning but results from a series of ritual activities over a longer period. This is also evident from instances where it has been possible to separate the ornamentation out into a series of successive decorative processes. The surface of the ‘ritual’ tools has apparently functioned as a wall or a board into which patterns have repeatedly been incised. This suggests that these artefacts had either a special ideological or ritual significance over an extended period. This conclusion is underlined by their smoothly worn surface and partially worn-away motifs. As a parallel to this approach, attention can be drawn to cave walls decorated with Late Palaeolithic art, where the same surfaces have been used repeatedly for painting or incising motifs. The fact that so few Ertebølle antler artefacts (relative to the total number of these tools known from the culture) are ornamented suggests that these pieces had a different function or worth than the non-ornamented examples. This interpretation is, however, contradicted to some degree by the evident damage to the axe edge, fractures at the shaft hole and evidence of heavy rejuvenation of these tools. Collectively, this shows that these tools have both been used in everyday life and in the same way as the unornamented examples. There are several instances of ornamented axes being heavily worn and having a damaged edge: For example, the axes found in the Ertebølle graves at Fannerup and Nederst on Djursland. This demonstrates they have both been used as actual tools and have had a symbolic value and significance that has remained intact despite their worn-out appearance. This leads to the conclusion that it has more probably been their function as a ritual object in a burial context that was crucial, while their use as a tool – an axe – has been of lesser significance. If we now turn our attention to the chronological aspects of these ornamented antler tools, it is interesting that virtually all of them can be dated to the earliest/Early Ertebølle culture, i.e 5.400 – 4600 B.C (cal.). The decoration of the antler tools (axes and shafts) of the Ertebølle culture in western Denmark largely ceases around 4700 BC, with a shift from ornamented to unornamented tools at the beginning of the Late Ertebølle culture. In the Middle and Late Ertebølle culture, decoration is only found on pottery and the painted/carved paddle blades, which apparently become the new objects for ornamentation. Ornamentation in the Late Ertebølle culture may, however, also have encompassed the human body and clothing, in addition to woven artefacts and those of skin/hide – all materials that are not readily preserved. This shift in, or cessation of, decoration of the culture’s antler artefacts constitutes a marked change relative to the way in which this material was treated for many centuries prior to this. It must, therefore, signify a change or a shift in the culture’s ideology at this time (c. 4700 BC). It also coincides with a decline in the culture’s burial practices – a virtual cessation, whereby the number of graves falls dramatically. This temporal coincidence may be just random chance, but it is interesting that it also coincides with the appearance of a series of new artefact Types in the material world of the Ertebølle culture: types that point towards the south and southeast: pottery, T-shaped antler axes, bone rings etc. This could mean that these events reflect a much deeper shift in the social and ideological structure of the Ertebølle culture than has previously been assumed, where research focus has largely been restricted to the typological/technological changes (see note 61). It seems that not only are there significant changes the Ertebølle culture’s material equipment around 4700 BC, but a much deeper, ideological social change occurs, which sees expression in significantly fewer graves and cessation of the decoration of antler axes and shafts.